Influence of Yoga on Blood Coagulation - Chohan, I S; Nayar, H S; Thomas, P; Geetha, N S (Thrombosis and Haemostasis, 1984)
Yoga is known to induce beneficial effects on physiological, biochemical and mental functions in man. Its effects on blood coagulation are not known. A study was conducted in seven previously untrained male adults who underwent a combination of yogic exercises, daily for one hour, over a period of four months. Parameters of blood coagulation were estimated before and after the end of yoga training. The following changes were observed: Fibrinolytic activity increased significantly with a concomitant fall in fibrinogen; activated partial thromboplastin time and platelet aggregation time were prolonged; blood and plasma platelets showed a rise; and both haemoglobin and heamatocrit were raised at the end of the training.These findings suggest that yoga induces a state of blood hypocoagulability. The impact of yoga on prevention of cardiovascular and thrombotic disorders is obvious.
Keywords: Yoga; Blood coagulation; Fibrinolysis; Platelets; Hypo-coagulability